Assessment of Toxicity of Ammonia on Mudskipper, Boleophthalmus Boddarti (Pallas, 1770): Preliminary Study - Ruhi Jaiswar; B. P. Chavan; P.P. Srivastava (Journal of Indian Fisheries Association, 2021)
Coastal waters, especially the intertidal zone, often receive a large quantity of agricultural runoﬀ, sewage, and industrial effluents, resulting in the accumulation of various toxic substances in the area. Thus, the fish and shellfish species inhabiting these areas are aﬀected and forced to migrate to other favourable areas. Mudskippers, the permanent inhabitants of the estuarine area, are fishes which can tolerate wide environmental changes, are also aﬀected and their population has decreased at many coastal locations. Ammonia is one of the most toxic substances, produced in polluted coastal aquatic ecosystems, and the mudskipper are still surviving in some of these areas. Hence, an attempt has been made to investigate the toxicity of ammonia in mudskipper Boleophthalmus boddarti. The fishes were exposed to varying concentrations of ammonia (0.1g/l to 0.9 g/l) under laboratory conditions for a period of 6 days. The rate of mortality of fishes was found to increase with increasing concentrations of ammonia. The LC50 (g/l) was found to be 0.5 which indicates that B. boddarti can tolerate high levels of ambient ammonia. This aspect needs further detailed research the fishes to higher temperature when ammonia and pH.